Data from: Using local ecological knowledge to build mutualistic networks in hyper-diverse and logistically challenging ecosystems - Ong, Lisa; Campos-Arceiz, Ahimsa; Kim R., McConkey (Dryad, 2021)
1. Collecting interaction data to build frugivory or seed
dispersal networks is logistically challenging in ecosystems that have
very high plant and animal diversity and/or where fieldwork is difficult
or dangerous. Consequently, the majority of available networks are from
ecosystems with low species diversity or they represent a sub-set of the
community.  2. Here, we propose an approach using local
ecological knowledge (LEK) of indigenous communities to build interaction
databases and weighted networks that would otherwise be difficult to
achieve with direct observations. Indigenous communities live and work in
many hyper-diverse ecosystems and the people within these communities
often have detailed knowledge of ecological processes.
3. Working in a Sundaland biodiversity hotspot – Royal Belum
State Park, Peninsular Malaysia – we used field data, visually-oriented
interviews with indigenous people (Orang Asli, in the Jahai and Temiar
ethnic subgroups), and published records to collate interactions, and
their frequency of occurrence of animal fruit consumption and seed
dispersal.  4. We documented 2060 fruit consumption and
1330 seed dispersal interactions among 164 plant species and 34 animal
taxa, the latter representing groups of closely related species or
individual species. The majority of the interactions (97%) were identified
by the LEK interviews, with the additional methods (field data and
published records) used to support and marginally expand the interview
data. The metrics for the networks we built reflect those of networks
structured by biological mechanisms, supporting the validity of our novel
method.  5. Local ecological knowledge is highly
relevant for building detailed databases for mutualistic interactions in
hyper-diverse and/or challenging ecosystems. Such ecosystems are among the
most vulnerable on earth, harbouring ecological interactions that are
often poorly documented at a community-level. We show how LEK can broaden
our knowledge of such sensitive ecosystems, but our approach is useful for
any ecosystem where people retain rich local ecological knowledge.
The method is fully described in Ong et al. (2021),
"Building ecological networks with local ecological knowledge in
hyper-diverse and logistically challenging
ecosystems". Further details are provided in the online
supplementary materials.
This dataset contains frugivory and seed dispersal interactions collected
largely based on local ecological knowledge provided by the indigenous
people of the Belum rainforest in Peninsular Malaysia, Sundaic region.
It includes fruit consumption and seed dispersal matrices tested
in Ong et al. (2021).
Keywords: FOS: Biological sciences